2021
DOI: 10.3390/app11083630
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Traveler’s Intentions to Use Public Transport during the COVID-19 Pandemic While Complying with Precautionary Measures

Abstract: Public transport use has drastically declined during the COVID-19 pandemic because the virus spreads through close contact with infected people and contaminated surfaces, especially in closed-environments. Evidence suggests that following the necessary safety guidelines can limit the spread of the virus, however, non-compliance to precautionary measures has been reported widely. Ignoring the precautionary measures may lead to quick transmission of the virus since public transport vehicles generally resemble cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
44
1
2

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(49 citation statements)
references
References 56 publications
2
44
1
2
Order By: Relevance
“… Study Data Country Focus Aloi et al (2020) Traffic counters, ticketing data Spain p.t. usage, mode share, travel distance Abdullah et al (2020) Online survey World Mode choice, trip purpose, travel distance Abdullah et al (2021) Questionnaire survey Pakistan Intention to use p.t. Awad-Núñez et al (2021) Online survey Spain Intention to use p.t.…”
Section: State Of the Artmentioning
confidence: 99%
See 1 more Smart Citation
“… Study Data Country Focus Aloi et al (2020) Traffic counters, ticketing data Spain p.t. usage, mode share, travel distance Abdullah et al (2020) Online survey World Mode choice, trip purpose, travel distance Abdullah et al (2021) Questionnaire survey Pakistan Intention to use p.t. Awad-Núñez et al (2021) Online survey Spain Intention to use p.t.…”
Section: State Of the Artmentioning
confidence: 99%
“…Despite in this work we consider the effects of the pandemic in general, some works analysed specific factors influencing changes in travel behaviour. Abdullah et al (2021) identified the relationships between the intention to use public transport and underlying factors, such as a positive relationship with the awareness about the disease. Dai et al (2021) analysed the effects of fare-free policies to increase subway ridership during the pandemic.…”
Section: State Of the Artmentioning
confidence: 99%
“…For answering the first research question and modeling street connectivity, two hierarchical multiple regression models were selected to find out the relationship between street connectivity and urban mobility features in Pakistani cities when socioeconomic variables are fixed in the models. Regression models were used in urban mobility literature by scholars [32,43,44]. Due to determine the optimal point in length-street density for having more active mobility (walking and cycling) and, answer the second research question, ROC analysis was applied and Youden Index was calculated.…”
Section: Methods Of Analysismentioning
confidence: 99%
“…The desire and attitude of residents to use public transportation during COVID-19 were studied in Lahore by employing regression models. The reduction tendency in using public transit was seen during the pandemic in Lahore [32]. The association of urban transportation and urban pollution was studied and compared before and after Coronavirus Pandemic in Pakistan by using the general regression model and Kruskal-Wallis H tests [33].…”
Section: Literature Reviewmentioning
confidence: 99%
“…The pandemic caused by the coronavirus has, like an earthquake, shaking the entire world and is still affecting the population globally. 1 It has affected all the segments of the society, the transportation sector included. While it has been necessary to ensure the same, and an even higher level of efficiency regarding the freight transport, first and foremost because of the transportation of medical supplies 2 , passenger transportation, especially public transport, has experienced limitations and even complete bans at certain points.…”
Section: Introductionmentioning
confidence: 99%